The effect of role ambiguity and role conflict on job performance in the hotel industry: The mediating effect of job satisfaction - Engin Üngüren; Serdar Arslan (Tourism & Management Studies)
Accommodation businesses are stressful workplaces due to their dynamic and demanding work environment. Role ambiguity and role conflict are major stress factors for hotel emplyees causing low levels of satisfaction, performance and high levels of turnover. The main purpose of this study was to explore the mediating effect of job satisfaction on the relationship between role conflict, role ambiguity and job performance. The data was collected by fully structured questionnaires from the employees who work in 4 and 5 star hotels in Alanya, one of the leading tourism destinations in Turkey. The data was analyzed via structural equation modeling. The results revealed that job satisfaction fully mediated the relationship between role ambiguity & role conflict and job performance. In line with the findings, managerial implications of findings, contributions, limitations, and future research directions were discussed.